The case for polygraph testing of sex offenders - Grubin, Don (Legal and criminological psychology, 2008)
Purpose. To describe the issues associated with the post-conviction testing of sex offenders (CST). Arguments. Post-conviction sex offender testing (PCSOT) is used widely in sex offender treatment and supervision programmes, but it is not without controversy. Much of the criticism of PCSOT, however, arises because of confusion between it and other applications of polygraphy. It is argued that the evidence for accuracy and utility, although not definitive, is sufficient to justify the use of PCSOT. Ethical issues are also addressed. Conclusion. Whatever the pros and cons of polygraph use in other settings, PCSOT can make a valuable contribution to sex offender treatment and management.